Endodontic Continuing Education of Dental Practitioners in Croatia: A Nationwide Survey - Sovic, Josipa; Segovic, Sanja; Matijevic, Jurica; Tomasic, Ivan (Open Access Macedonian Journal of Medical Sciences, 2024)
AIM: This study aims to assess the state of endodontic continuing education (ECE) among dental practitioners in Croatia and identify factors influencing participation in such education. METHODS: A questionnaire was sent to all dental offices in Croatia, yielding 819 responses. The data were analyzed descriptively and statistically modeled. RESULTS: Most respondents had participated in some form of ECE during their careers. However, in the past 5 years, only about 78% had engaged in such education, with participation decreasing by 2% for each additional year of practice. Male practitioners had significantly less continuing education in the past 5 years, particularly in private clinics, dental clinics with concession contracts, and certain regions. Practitioners who performed more endodontic treatments reported higher levels of continuing education. The endometer was the only modern technique consistently used by about 60% of practitioners with continuing dental education. CONCLUSION: Continuing education in endodontics should be more strongly promoted among practitioners with longer careers, particularly men.